Propentofylline reduces glial scar development following gliotoxic damage in the rat brainstem - Bondan, Eduardo Fernandes; Martins, Maria de Fátima Monteiro; Dossa, Pietro Domingues; Viebig, Lígia Bocamino; Cardoso, Carolina Vieira; Martins, João Lopes, Júnior; Bernardi, Maria Martha (Arquivos de Neuro-Psiquiatria, 2016)
Propentofylline is a xanthine derivative that depresses activation of glial cells, whose responses contribute to neural tissue damage during inflammation. Ethidium bromide injection into the central nervous system induces local oligodendroglial and astrocytic loss, resulting in primary demyelination, neuroinflammation and blood-brain barrier disruption. Surviving astrocytes present a vigorous reaction around the injury site with increased immunoreactivity to glial fibrillary acidic protein (GFAP). Objective This study aimed to evaluate the effect of propentofylline administration on astrocytic response following gliotoxic injury.Method Wistar rats were injected with ethidium bromide into the cisterna pontis and treated or not with propentofylline (12.5mg/kg/day, intraperitoneal) during the experimental period. Brainstem sections were collected from 15 to 31 days after gliotoxic injection and processed for GFAP immunohistochemistry.Results and Conclusion Results demonstrate that propentofylline decreased astrocytic activation until the 21st day, suggesting that this drug may have a role in reducing glial scar development following injury.
Keywords: astrocytes; ethidium; gliosis; gliotoxin; xanthine